Comparative evaluation between two nutritional supplements in the improvement of telogen effluvium - Sant'Anna Addor FA; Coelho Donato L; Abreu Melo CS (Dove Medical Press, 2018)
Flávia Alvim Sant’Anna Addor,1 Ludmila Coelho Donato,2 Camila Sirieiro Abreu Melo2 1MEDCIN Research, Osasco, Brazil; 2Clinical Research, Farmoquímica S.A, Rio de Janeiro, Brazil Purpose: Telogen effluvium (TE) is defined as a diffuse hair loss characterized by shortening of the anagen phase and precipitation of the telogen phase, with a consequent reduction of total hair volume. Nutritional supplementation is indicated under conditions in which TE is related to dietary disorders. The aim of this clinical study was to compare the efficacy of two different supplements in monotherapy for TE.Patients and methods: Female adult patients were randomized to receive two oral nutritional supplements (group 1: a supplement composed of zinc, biotin, iron, vitamins A, C, E, and B complex, folic acid, magnesium, and amino acids of keratin and collagen and group 2: calcium pantothenate cystine, thiamine nitrate, medicinal yeast, keratin, and aminobenzoic acid) to treat hair loss for 180 days. They were evaluated clinically and by digital trichoscopy.Results: Clinical evaluation showed significant clinical improvement (P<0.05) for the evaluated parameters: hair loss, hair volume, density of hair (scalp cover), hair shine, hair strength, in 180 days. At 90 days evaluation, group 1 showed significant improvement for all parameters, while group 2 did not show any significant improvement for hair shine and hair strength. In the digital trichoscopy, there was a significant improvement only in group 1 (11.09%×7.76%) after 180 days.Conclusion: In idiopathic TE, the nutritional component should be suspected; the supplementation of an association of nutrients in recommended daily intake can lead to significant improvement of the condition from the first trimester of use. The use of an association with proven efficacy and a safety profile and posologic convenience facilitate its indication and patient adherence. Keywords: telogen effluvium, supplementation, trichoscopy, hair loss